The prevalence of Refractive Errors Among Medical Students and The possible Associated Risk Factors: A Systematic Review - Alrawashdeh, Mohammad; A'saf , Sura; Alramahi, Osama; Momani, Moath; Alzu’bi, Ali; Bani khalaf, Mohammad; Alrabadi, Faris; Alsalman, Hashim (Journal of Neonatal Surgery, 2025)
Refractive errors are a global health problem especially in students with high education such as Medicine. Therefore, the prevalence of Refractive errors in medical students in addition to the contributing risk factors have been discussed by numerous studies worldwide. In this systematic review we provide data about the prevalence of refractive errors including myopia, hyperopia and astigmatism and the possible associated factors: family history, gender, physical activity, diet, types of lights and others